Students’ Interpersonal Meaning Towards Podcast -Assisted Listening Learning: An Appraisal Perspective - Siti Fajriyah; Yuna Tresna Wahyuna; Totoh Tauhidin Abas (Peneliti.net, 2021)
Podcasts are a medium that can help teachers and students in distance learning or electronic learning. Podcasts can help teachers provide learning material and students can access it on each of the devices they have. Podcasts can also help students in learning English, especially in listening skills. This study aims to understand students’ interpersonal meaning focus on attitude towards podcast assisted listening learning. The researcher used a qualitative narrative inquiry design in this research to discover data from real-life situations. The instruments of this research were interview and diary. The collecting data was obtained through Google meeting. The researcher took place the research at Senior High School in Karawang. The participants of this research were four students of the 3rd grade at senior high school in Karawang. The questions were asked by semi structured interview. The findings revealed that the students’ attitude towards podcast assisted listening learning which include by three components, namely: affect, judgement and appreciation. Affect contain by students’ feeling, judgement contains by normality, capacity, tenacity, veracity, propriety and appreciation contains by quality, composition, and valuation